Self-Monitoring of Health-Related Goals in Older Adults with Use of a Smartphone Application. Issue 2 (2nd April 2016) - Steinert, Anika; Haesner, Marten; Tetley, Aileen; Steinhagen-Thiessen, Elisabeth
Abstract : Self-monitoring can motivate older adults to achieve health-related goals. The aim of the study was to identify the benefit of self-monitoring with a smartphone application for older adults. Thirty seniors set individual health-related goals. Over a period of 4 weeks, participants were continually reminded of their goals. Evaluation of the subjective benefits varied across types of individual goals. Some features showed significant subjective benefits. Currently, mobile applications for self-monitoring are used by only a small part of the elderly. In order to promote this usage, barriers, and user experience need to be considered.